The Relationship Between Parenting Patterns In Fulfilling Nutrition With Body Weight In Toddlers - Telova, Yurizki (Universitas Dehasen Bengkulu, 2025)
Growth is a quantitative change. Monitoring the growth and development of toddlers can be done through active visits to Posyandu. One of the things that can affect growth in children is parenting. Good parenting from parents will improve optimal nutritional status conditions. Eating behavior in children is a reflection of parenting patterns from parents. Mothers have a role in the nutrition of toddlers, their parenting patterns also play a role in the occurrence of growth disorders. Research Objective: To determine whether there is a relationship between parenting patterns in fulfilling nutrition with body weight in toddlers. Research Design: Analytic with Cross Sectional approach. Population: All toddlers in Hilimbosi Village as many as 114 people. Sample: 52 people with Simple Random Sampling technique. Instrument: Questionnaire and KMS sheet. Data Analysis: Mann-Whitney Test statistical test. Results: Parents with democratic parenting are 42.3%, parents with authoritarian parenting are 25.0% and parents with permissive parenting are 32.7%, the appropriate weight of toddlers is 75.0%, and the weight of toddlers is not appropriate as much as 25.0%. Conclusion: There is no relationship between parenting patterns in fulfilling nutrition with body weight in toddlers (p = 0.605). Suggestion: It is recommended for parents to pay more attention to the nutritional content of the food consumed by children by maintaining good parenting and continuing to monitor Bali's growth.